Elephant’s toothpaste: review of exciting chemistry learning in senior high school - I S Hardyanti; I Nurani; D S Hardjono HP; Sudarmin Sudarmin (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Innovative and creative learning can be done through simple demonstrations to strengthen the understanding of chemical concepts. One simple demonstration is Elepanth's Toothpaste experiment which can train students to apply knowledge in investigating and explaining the effect of temperature, pH, enzyme concentration, substrate concentration on reaction rate with catalyst. The purpose of writing is to provide a reference in teaching chemistry with fun methods. The Elepanth's toothpaste experiment undergoes a hydrogen decomposition reaction into water and oxygen gas by yeast or potassium iodide which is the source of the catalase enzyme. Yeast or potassium iodide acts as a catalyst by decreasing the activation energy, so the reaction is easy to occur. Foam is formed by the reaction between oxygen and detergent in water, which increases in number as the concentration and strength of the catalyst increases. Implementation of elephant's toothpaste experiment in school can be done with problem-based learning model, where students are taught to further improve concept understanding with problem solving. The existence of chemistry learning with elephant's toothpaste experiments is expected to improve understanding of chemical concepts and create enjoyable learning.